The effect of oxidative stress towards the expressions of thiamine biosynthesis genes (THIC & THI1/THI4) in oil palm (Elaeis guineensis Jacq.) - Che Idris, Zainor Hafisah (2015)
Thiamine is known to be important in human diet and its cofactor is required for the vital metabolic processes such as acetyl-CoA biosynthesis, amino acid biosynthesis, and Krebs and Calvin cycle. The active cofactor is thiamine pyrophosphate (TPP). There are findings about TPP which can act as a non-cofactor function which is as stress-response molecule. In this study, the level of expression of THIC and THI1/THI4 gene transcripts upon induction of oxidative stress in oil palm was observed. The gene transcripts for the first two enzymes in the biosynthesis pathway, THIC and THI1/THI4 were successfully identified and amplified. Primers were designed based on the comparison of different plants such as Arabidopsis thaliana, Zea mays, Oryza sativa, and Alnus glutinosa. Also, the expression of these thiamine biosynthesis genes were investigated in response to the stress given to the oil palm. The gene transcripts’ expressions were analyzed via RT-PCR over a time point after the application of paraquat. As the oxidative stress induced the expression of the THIC gene transcript was increased by 20 % and the production of THI1/THI4 gene transcript was increased by 10 % upon the induction of oxidative stress. Thus, these findings support the suggestion that thiamine may play a role in plant protection against stress as it may lead to the overexpression of thiamine in general.